Interpolation methods for multivalued functions: Dedicated to Professor Gheorghe Coman on the occasion of his 80th anniversary - SOMOGYI, Ildiko; SOÓS, Anna (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
The aim of these article is to study the interpolation problem for multi- valued functions. We give some methods for the approximation of these functions. Mathematics Subject Classification (2010): 65D05, 65D07.